Utilization of Youtube Media in Fostering Young Farmer Interest In Chili Farming in Ciamis Regency - Kosmana, Engkos; Raya, Alia Bihrajihant; Kaliky, Rahima (University of Jember, 2024)
The presence of the youtube platform makes it easier for farmer children to access agricultural information. The high use of youtube among farmer children will promote their attitudes, motivation, perceptions of chilli farming and increase their interest in continuing chilli farming. Therefore, it is necessary to conduct research to analyse the effect of the use of youtube directly or through the variables of attitude, motivation and perception on the interest in continuing chilli farming in Ciamis Regency. The research was carried out using a descriptive quantitative approach. The data were collected through a survey using a questionnaire, involving a sample of 100 children of farmers, taken by simple randomisation in 5 sub-districts of Ciamis Regency. Testing using SEM Partial Least Square with SMART PLS software. From the results of the study it is known that the variables of youtube use, motivation, attitudes and perceptions have a direct positive and significant effect on the interest of farmers' children in continuing chilli farming, youtube use has a direct positive and significant effect on the motivation, attitudes and perceptions of chilli farming, and youtube use has an indirect significant effect on the interest of farmers' children in continuing chilli farming through the motivation and perceptions of farmers' children towards chilli farming.